Surgical treatment of retroperitoneal neuroblastoma in children. Clinical experience - S. A. Kuznetsov; E. N. Kolesnikov; A. N. Shevchenko; Yu. Yu. Kozel; G. A. Mkrtchyan; M. V. Starzhetskaya; A. I. Bespalova; E. E. Pak; D. Yu. Yurchenko; O. P. Popovyan (Южно-Российский онкологический журнал, 2022)
Purpose of the study. Was to analyze our experience of surgical treatment of retroperitoneal neuroblastoma in children and the influence of radical surgical treatment on the disease outcomes.Materials and methods. The study included 35 patients (14 girls and 21 boys, mean age 3.3 years) receiving treatment for retroperitoneal neuroblastoma at the Department of Pediatric Oncology, National Medical Research Centre for Oncology, in 2016–2018. 32 patients underwent surgical treatment. The disease progression during neoadjuvant polychemotherapy was registered in 3 patients. Initially, surgery was performed in 5 patients; the rest of the patients underwent percutaneous trepan biopsy with immunohistochemical testing and subsequent neoadjuvant polychemotherapy. No patients developed complications in the early postoperative period. In the article, we present our experience in the surgical treatment of pediatric patients with retroperitoneal neuroblastomas.Results. Patients have been observed during 12 to 24 months. 23 of 28 radically operated patients are alive and have no signs of the disease recurrence or progression. 2 patients developed tumor recurrence and received anti-recurrence PCT and DGT. Currently the patients are in remission. 3 patients showed systemic progression due to primarily advanced disease.Conclusion. Administration of modern surgical techniques and instrumentation allows radical surgical treatment for a large percentage of patients with locally advanced neuroblastoma.